Appropriate illustrations for appropriate functions : the taxonomy of illustration - Sheik Said, Normahdiah (Universiti Putra Malaysia Press, 2011)
Illustrations play an important role in depicting information. As we move deeper and deeper into the world of visualisation, illustrations play a vital role especially in the learning paradigm. More and more users use illustrations to convey messages or information to promote sales, to campaign an idea, to decipher a belief or teach a lesson because theories have shown that things that are visualised are learned more easily. Educationalists and many researches have supported this theory. Psychologists have found that people retain visual information longer than verbal information. It has been found that visual memories are more effective compared to all the different elements of memory such as radio, olfactory and tactile.Knowing appropriate illustrations for appropriate functions will help us get the right message across the right audiences at the right time and the right place. Therefore this book is useful to students in colleges or universities, editors and reviewers of printed and non-printed materials, beginners from the team of industrial and book designers; text designers and interface designers, graphic artists and graphic designers as well as those interested in making it right when it comes to visual representations.